Implementation of the Gender and Equity Certification Requirement under the Public Finance and Management Act - Initiative for Social and Economic Rights (ISER) (Initiative for Social and Economic Rights (ISER), 2016)
Uganda’s Public Finance and Management Act 2015 mandates the Ministry of Finance, Planning and Economic Development (MoFPED) and the Equal Opportunities Commission (EOC), to issue a certificate that attests to the gender- responsiveness and equity of the annual budget. Additionally, the Act provides for measures to be taken to ensure equal opportunities for men, women, Persons With Disabilities (PWDs) and other marginalized groups to participate in the budget process. In this issue, ISER provide an analysis of the assessment undertaken by the EOC into the gender and equity- responsiveness of Government Ministries, Departments and Agencies (MDAs). The Chairperson of the EOC, Ms. Sylvia Muwebwa Ntambi reveals in a Q&A that the Commission intends to invest in capacity building for all MDAs and will regularly dialogue with relevant authorities to strengthen the effectiveness of the certification process. The Director of Budget at the MoFPED, Mr. Kenneth Mugambe, who also responded to a Q&A, speaks about the strides made in gender and equity budgeting despite resource constraints. Mr. Mugambe applauds the existing legal framework, which in his view does seek to achieve the “progressive realization” of social and economic rights. Mr. Aliyi Walimbwa, a Senior Planner from the Ministry of Health, shares his ministry’s efforts to embed the gender and equity certification framework in healthcare practice; Ms. Ceaser Nabwire provides insights into how gender budgeting is currently occurring at local government level; and Ms. Irene Navuga from the Southern and Eastern Africa Trade, Information and Negotiation Institute (SEATINI) writes about how tax policies can contribute to the attainment of gender equality. From the field, we share highlights from ISER’s gender budgeting capacity building workshops, which were hosted for women’s groups in Kayunga District.